Analisis Kualitas Pelayanan dan Brand Image Terhadap Minat Kunjungan Ulang Pasien Klinik Bidan Marlina - Rasyid, Harun Al; Indah K, Agus Tri (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2019)
This study aimed to analyze the influence of service quality and brand image to re-visit interest. Samples were patients who were ambulatory and hospitalized at the Clinic Bidan Marlina Tangerang Selatan totaling 130 respondents. Regression analysis techniques were used to analyze the influence of service quality and brand image to re-visit interest is using SPSS (Statistical Package for the Social Sciences). Service quality and significant positive effect on the re-visit interest in Bidan Marlina Clinic Tangerang Selatan, every 1% increase in the variable quality of service will be followed by the increase in re-visit interest of 0.265 percent. While the brand image variable positive and significant effect on the interest re-visit the clinic Bidan Marlina Tangerang Selatan, every 1% increase in variable brand image will be followed by the increase in re-visit interest of 0.740 percent. Furthermore, the results also showed that there is a positive and significant influence on the independent variables of service quality and brand image together to re-visit interest. Service quality and brand image affects 65.7% of the interest to re-visit the clinic Bidan Marlina Tangerang Selatan.